2020
DOI: 10.1007/s10586-020-03190-3
|View full text |Cite
|
Sign up to set email alerts
|

Privacy protection for fog computing and the internet of things data based on blockchain

Abstract: With the development of the Internet of Things (IoT) field, more and more data are generated by IoT devices and transferred over the network. However, a large amount of IoT data is sensitive, and the leakage of such data is a privacy breach. The security of sensitive IoT data is a big issue, as the data is shared over an insecure network channel. Current solutions include symmetric encryption and access controls to secure the data transfer, but they have some drawbacks such as a single point of failure. Blockc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…The authors created a client and web services application that allows users to store and exchange provenance information in a BC using open standards [ 146 ]. To protect IoT data, Liu et al [ 188 ] presented a decentralized access control mechanism based on BC with FC integration. To encrypt IoT data before uploading to the cloud, this technique employs mixed linear and nonlinear spatiotemporal chaotic models, as well as the least significant bit.…”
Section: Blockchain-fog Computing Purposesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors created a client and web services application that allows users to store and exchange provenance information in a BC using open standards [ 146 ]. To protect IoT data, Liu et al [ 188 ] presented a decentralized access control mechanism based on BC with FC integration. To encrypt IoT data before uploading to the cloud, this technique employs mixed linear and nonlinear spatiotemporal chaotic models, as well as the least significant bit.…”
Section: Blockchain-fog Computing Purposesmentioning
confidence: 99%
“…For BC, privacy-preserving strategies based on encryption approaches are evolving, allowing users to become anonymous and have the ability to manage their personal data (e.g., what, whom, and when personal data can be shared in each transaction). Authors proposed several mechanisms to enhance privacy ([ 70 , 88 , 115 , 116 , 162 , 169 , 217 ]); to enable and enhance identification ([ 61 , 129 , 136 , 172 , 174 , 209 , 218 ]), to ensure data privacy ([ 97 , 146 , 188 ]), and to enhance location privacy ([ 83 , 165 , 192 , 198 ]). The majority of the selected studies under this category reported that BC can enhance the level of privacy, in general, followed by identification, and the least purpose mentioned was to achieve data privacy.…”
Section: Blockchain-fog Computing Purposesmentioning
confidence: 99%
“…Fog computing can regulate privacy [17]. Sensitive user data may be evaluated locally instead of centralized cloud infrastructure.…”
Section: Privacymentioning
confidence: 99%
“…At the same time, these devices, which we unconditionally trust as our digital continuation, constantly interact with each other. The Internet of Things (IoT), defined as "a system of interconnected computing devices with unique identifiers (UIDs) [that] can perform data communications without any human involvement" (Liu et al, 2021(Liu et al, , p. 1331, as well as communication between gadgetswhen your refrigerator can exchange data with your fitness bracelet, for examplefurther exacerbate the problem. For example, some researches have shown that with the advent of the IoT, the possibility of using big data as a source of official statistics is increasingly being considered, creating additional ethical and statistical problems (Tam & Kimb, 2018).…”
Section: The Essence Of These Changesmentioning
confidence: 99%